Vaccines in Veterinary Medicine: A Brief Review of History and Technology - McVey, Scott (Vet Clin North Am Small Anim Pract, 2010)
The use of vaccines in veterinary medicine has progressed from an experimental adventure to a routine and relatively safe practice. The common and aggressive use of efficacious vaccines has been responsible for the control and eradication of several diseases. Despite progress in research technologies, diagnostic capabilities, and manufacturing methods, there remain many infectious diseases for which no effective vaccines exist. Global availability, field compliance, effectiveness, and safety are also significant concerns. This review addresses the history, current practices, and potential future improvements of vaccine use in veterinary medicine.